DNA Barcode for the Parthenogenetic Surinam Cockroach Pycnoscelus surinamensis (Linnaeus, 1758) (Blattodea: Blaberidae) from India - Shabnam, A; Dinesh, K P (International Research Journal of Insect Sciences, 2022)
DNA Barcoding is one of the emerging tools in molecular identification of faunal diversity, specifically insect fauna. The Surinam cockroach, Pycnoscelus surinamensis is the only known roach to be obligatorily parthenogenetic, with reported haplotypes. P. surinamensis is well established in Indomalayan, tropical and subtropical regions and substantially documented from India with a phenetic approach. Herewith we report the first set of mt DNA barcode from a vouchered collection for the species from southern Western Ghats India. Discussions are made on the identity of two sequences each of Blatteria species and Pycnoscelus species reported from USA.